Flow cytometric analysis of leukemic blast cells in pediatric B-cell precursor acute lymphoblastic leukemia with translocation t(12;21)(p13;q22)/ETV6-RUNX1 - Zh. V. Permikin; A. M. Popov; T. Yu. Verzhbitskaya; Т. О. Riger; O. R. Arakaev; A. A. Vlasova; Yu. V. Olshanskaya; A. N. Kazakova; S. V. Tsvirenko; L. I. Saveliev; G. A. Tsaur; L. G. Fechina (Онкогематология, 2019)
The objective of the study was searching for surface antigen expression that could predict presence of translocation t(12;21)(p13;q22)/ETV6RUNX1 in pediatric B-cell precursor acute lymphoblastic leukemia patients.Results . ETV6-RUNX1 fusion gene transcript was revealed in 118 (22.4 %) out of 526 children with B-cell precursor acute lymphoblastic leukemia. Leukemic blast cells in ETV6-RUNX1-positive patients more frequently had high CD10 expression, myeloid markers co-expression , including CD13, CD33, CD117, and absence of CD20 than in ETV6-RUNX1-negative ones. Nevertheless diagnostic test performance characteristics of each single parameter was not strong enough for predicting the presence of translocation t(12;21)(p13;q22)/ETV6-RUNX1.Conclusion . Thus application of conventional set of immunological markers does not allow reliable distinguishing this patients’ subgroup. However antibodies panel enlargement, high degree of flow cytometry standardization and additional analytical methods can potentially improve applicability of antigen profile analysis for separation of patients with translocation t(12;21)(p13;q22)/ETV6-RUNX1.